Estrategias metodológicas en época de covid-19 en el nivel inicial 2 de la Unidad Educativa Combatientes de Tapi, de la ciudad Riobamba, provincia Chimborazo - Sánchez Tipan, Ana Damaris (2023)
The present research work with the theme "Methodological strategies in the time of COVID- 19 in the initial level 2 of the Combatientes de Tapi Educational Unit, Riobamba City, Chimborazo Province", emphasizes the development of methodological strategies for children from 4 to 5 year-old as an essential tool for their teaching-learning process. Said analysis will allow teachers to search for better resources and materials adaptable to any learning environment through methods, techniques and processes that are consistent with the reality of the students. Methodologically, a qualitative approach of a descriptive and documentary type was used by obtaining information from a bibliographic analysis of different sources such as: magazines, digital repositories, scientific articles and books, For this investigation, we worked with a population of 20 children, beginning with the collection of data at the scene, for which the observation technique was used, as an instrument a file was applied, a key sheet to obtain essential information. The first results allowed us to appreciate the lack of application of easy- to-understand strategies that dynamically encourage frequent use of the mask to prevent the spread of the virus in infants. The discussion arises in the lack of accompaniment of the parents during the synchronous classes, and therefore methodological strategies are proposed where the role of the adult is to participate with the child. Concluding that they are important to guarantee knowledge and significant learning from any scenario or training environment.